PENGARUH INFRASTRUKTUR (JEMBATAN) TERHADAP PEREKONOMIAN DI PROVINSI ACEH - M. Rayyan Rivalda; Eddy Gunawan (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2019)
Abstract This study aims to examine the effect of district / city infrastructure (bridges) in aceh province on the economy in aceh province, where infrastructure will absorb labor, so in this study there are 1 dependent variable and 2 independent variables, gdp as the dependent variable in this study while bridge length and number of workers as independent variables. Based on the multiple linear regression model, using panel data from 23 districts / cities in aceh from 2011 to 2015 and also using the fixed effect model (fem) approach. The results show that the variable effect of bridge length does not have a significant effect on the aceh province grdp while the number of workers has a positive and significant influence on the aceh province grdp.Keywords:   Infrastructure, Bridges, And Economy In Aceh Province, and Fixed Effect Model.